Factores Socioculturales Relacionados con La Violencia de Pareja, Huamachuco-2012 - Asto Campos, Paola Melina (2012)
This quantitative investigation was cross-sectional in women 18 to 45 years Huamachuco District, listed on the JUVESC and Rounds campesins , Huamachuco urban district, in order to determine the influence of sociocultural factors: age, occupation, marital status, level of education, the type of partner violence. The conclusions were arrived were: 1. The age of the women in this study was mostly (30.7%) youth group (18-24yrs) and 31-38 years (28.9%), the occupation was mostly indoors (72.8%) and marital status was with a partner (76.3%). According to the educational attainment level of 57.9% with secondary and higher education. The 42.1% no education (primary and illiterate).4 2. The type of psychological violence was mostly mild to moderate percentage (56.1%, 29.8% respectively). Physical violence was mostly mild (64%) and moderate at 9.6%. Sexual violence was 36.8% moderately.5 3. The Age, Occupation, not influence the type of partner violence, whether physical, psychological and sexual.6 4. The status does not influence the type of intimate partner physical and psychological but influences the type of sexual violence. 5. The level of education influences the type of physical violence but not in psychological sexual.